2016
DOI: 10.1177/1540796916661492
|View full text |Cite
|
Sign up to set email alerts
|

Ecobehavioral Characteristics of Self-Contained High School Classrooms for Students With Severe Cognitive Disability

Abstract: This study investigated educational experiences for students with significant cognitive disability (SCD) taught in self-contained high school classrooms. Nineteen students and nine teachers across five high schools and four school districts participated. A time-sampling method was used to describe the ecological, teacher, and student behaviors of these classrooms. Field notes were collected and analyzed as well. Results revealed that students in these classrooms were often passively engaged and had few opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 38 publications
9
59
0
1
Order By: Relevance
“…Although placement data are readily available for each of our countries, physical placement does not adequately address the degree to which students access and benefit from their education. Despite the promises of individualization and support in special education settings, several researchers have established that self-contained settings offer a high level of distraction, fewer opportunities to respond to instructional cues, and a lack of tailored instruction for individual students (Causton-Theoharis, Theoharis, Orsati, & Cosier, 2011;Kurth, Born, & Love, 2016). In contrast, general education settings offer increased opportunities to learn, benefit from targeted instruction, and interact with typical peers (Hehir et al, 2016McDonnell, Thorson, & McQuivey, 2000Taub, McCord, & Ryndak, 2017).…”
Section: Inclusive Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although placement data are readily available for each of our countries, physical placement does not adequately address the degree to which students access and benefit from their education. Despite the promises of individualization and support in special education settings, several researchers have established that self-contained settings offer a high level of distraction, fewer opportunities to respond to instructional cues, and a lack of tailored instruction for individual students (Causton-Theoharis, Theoharis, Orsati, & Cosier, 2011;Kurth, Born, & Love, 2016). In contrast, general education settings offer increased opportunities to learn, benefit from targeted instruction, and interact with typical peers (Hehir et al, 2016McDonnell, Thorson, & McQuivey, 2000Taub, McCord, & Ryndak, 2017).…”
Section: Inclusive Educationmentioning
confidence: 99%
“…Similar to criticisms of the Swedish alternate curricula for lacking adequate challenge or analyses of student learning, self-contained classes in the United States have also been criticized for spending too little time on instruction as well as an emphasis on skills taught out of context (Causton-Theoharis et al, 2011; Kurth et al, 2016). As in Sweden, there is a tradition in the United States of prioritizing "life skills" over academic skills (Browder et al, 2004;Timberlake, 2014).…”
Section: Life Skills Over Academic Skillsmentioning
confidence: 99%
“…Students taught in more restrictive settings may experience less rigorous standards-based instruction (Bacon, Rood, & Ferri, 2016) and have less rigorous individualized education program (IEP) goals (Kurth & Mastergeorge, 2010) than students taught in general education settings. For example, students may be more passively engaged in learning (Pennington & Courtade, 2015), learn in distracting environments with limited access to grade-referenced curriculum (Kurth, Born, & Love, 2016), and receive more limited specialized instruction (Causton-Theoharis, Theoharis, Orsati, & Cosier, 2011) than students who are taught in general education settings. Ruppar, Fisher, Olson, and Orlando (2018) found that students with ESN were 10 times more likely to be exposed to academic literacy content in general education settings than in more restrictive settings.…”
mentioning
confidence: 99%
“…Terdapat dua kendala yang sering yang mempengaruhi implementasi intervensi berbasis inklusi terkait guru dan ruang kelas (Koegel dkk., 2011). Persepsi guru tentang keyakinan pribadi mereka tentang pedagogi, kesesuaian yang dirasakan intervensi untuk siswa tertentu, dan ketersediaan bahan yang diperlukan dapat mempengaruhi implementasi intervensi (Kurth, Born, & Love, 2016). Penelitian dilakukan di setting kelas reguler.…”
Section: Pembahasanunclassified